Commercial polycarbonate track-etched membranes as substrates for low-cost optical sensors - Martínez-Pérez, Paula; García-Rupérez, Jaime (Beilstein Journal of Nanotechnology, 2019)
Porous materials have become one of the best options for the development of optical sensors, since they maximize the interaction between the optical field and the target substances, which boosts the sensitivity. In this work, we propose the use of a readily available mesoporous material for the development of such sensors: commercial polycarbonate track-etched membranes. In order to demonstrate their utility for this purpose, we firstly characterized their optical response in the near-infrared range. This response is an interference fringe pattern, characteristic of a Fabry–Pérot interferometer, which is an optical device typically used for sensing purposes. Afterwards, several refractive index sensing experiments were performed by placing different concentrations of ethanol solution on the polycarbonate track-etched membranes. As a result, a sensitivity value of around 56 nm/RIU was obtained and the reusability of the substrate was demonstrated. These results pave the way for the development of optical porous sensors with such easily available mesoporous material.
Keywords: chemical sensor; Fabry–Pérot interferometer; optical sensor; polycarbonate; track-etched membrane

(untitled) - Zhang, Y.-n.; Zhao, Y.; Zhou, T.; Wu, Q. (Lab Chip, 2018)

(untitled) - Ruiz-Tórtola, Á.; Prats-Quílez, F.; González-Lucas, D.; Bañuls, M.-J.; Maquieira, Á.; Wheeler, G.; Dalmay, T.; Griol, A.; Hurtado, J.; Bohlmann, H.; Götzen, R.; García-Rupérez, J. (J. Biophotonics, 2018)

(untitled) - Caroselli, R.; Martín Sánchez, D.; Ponce Alcántara, S.; Prats Quilez, F.; Torrijos Morán, L.; García-Rupérez, J. (Sensors, 2017)

(untitled) - Prabowo, B. A.; Purwidyantri, A.; Liu, K.-C. (Biosensors, 2018)

(untitled) - Caroselli, R.; Ponce-Alcántara, S.; Prats Quilez, F.; Martín Sánchez, D.; Morán Torrijos, L.; Griol Barres, A.; Bellieres, L.; Bandarenka, H.; Girel, K.; Bondarenko, V.; García-Rupérez, J. (Opt. Express, 2017)

(untitled) - Levitsky, I. A. (Sensors, 2015)

(untitled) - Ponce-Alcántara, S.; Martín-Sánchez, D.; Pérez-Márquez, A.; Maudes, J.; Murillo, N.; García-Rupérez, J. (Opt. Mater. Express, 2018)

(untitled) - Qiu, H.-J.; Li, X.; Xu, H.-T.; Zhang, H.-J.; Wang, Y. (J. Mater. Chem. C, 2014)

(untitled) - Shindell, O.; Mica, N.; Ritzer, M.; Gordon, V. D. (Phys. Chem. Chem. Phys., 2015)

(untitled) - Párraga-Niño, N.; Quero, S.; Ventós-Alfonso, A.; Uria, N.; Castillo-Fernandez, O.; Ezenarro, J. J.; Muñoz, F.-X.; Garcia-Nuñez, M.; Sabrià, M. (Talanta, 2018)

(untitled) - Martín-Sánchez, D.; Ponce-Alcántara, S.; Martínez-Pérez, P.; García-Rupérez, J. (J. Electrochem. Soc., 2019)

(untitled) - Wilson, R. H.; Nadeau, K. P.; Jaworski, F. B.; Tromberg, B. J.; Durkin, A. J. (J. Biomed. Opt., 2015)

(untitled) - Aran, K.; Sasso, L. A.; Kamdar, N.; Zahn, J. D. (Lab Chip, 2010)

(untitled) - García-Rupérez, J.; Toccafondo, V.; Bañuls, M. J.; García Castelló, J.; Griol, A.; Peransi-Llopis, S.; Maquieira, Á. (Opt. Express, 2010)

(untitled) - Sani, E.; Dell'Oro, A. (Opt. Mater., 2016)

(untitled) - Ooi, C. H.; Bormashenko, E.; Nguyen, A. V.; Evans, G. M.; Dao, D. V.; Nguyen, N.-T. (Langmuir, 2016)

(untitled) - Ogończyk, D.; Jankowski, P.; Garstecki, P. (Lab Chip, 2012)

(untitled) - Kosobrodova, E.; Jones, R. T.; Kondyurin, A.; Chrzanowski, W.; Pigram, P. J.; McKenzie, D. R.; Bilek, M. M. M. (Acta Biomater., 2015)

(untitled) - Godeau, G.; Amigoni, S.; Darmanin, T.; Guittard, F. (Appl. Surf. Sci., 2016)

(untitled) - Sultanova, N. G.; Kasarova, S. N.; Nikolov, I. D. (Opt. Quantum Electron., 2013)